Studi In Silico Senyawa Kimia Zingiber Montanum J.König sebagai Antidiabetes terhadap Reseptor α-Glukosidase - Ninu Eltriya; Rosa Adelina; Ismiarni Komala (Pharmaceutical and Biomedical Sciences Journal (PBSJ), 2024)
Diabetes Mellitus (DM) is a metabolic disorder resulting from the impaired secretion of insulin, glucagon, and other hormones, leading to elevated blood sugar levels. Bangle (Zingiber montanum) is recognized for its potent antidiabetic compounds. This study sought to evaluate the potential and interaction of chemical compounds from bangle on the α-glucosidase receptor as an antidiabetic using molecular docking studies. The molecular docking analyses were conducted using Autodock Vina software and Biovia Discovery Studio Visualizer for 2D and 3D visualization. Fifteen chemical compounds from the bangle plant were subjected to molecular docking studies against the α-glucosidase receptor, with the comparative ligand acarbose. Results indicated that acarbose demonstrated a bond energy (ΔGbind) of -6.9 cal/mol. Conversely, six test compounds, including cassumunarin A (-7.7 kcal/mol), cassumunarin B (-7.5 kcal/mol), cassumunarin C (-8.0 kcal/mol), cassumunin A (-7.0 kcal/mol), cassumunin C (-7.0 kcal/mol), and banglenol A (-6.9 kcal/mol), exhibited lower binding energy than acarbose, signifying a more stable bond conformation and a stronger effect. These compounds formed hydrogen bonds with the amino acids Asp327, Asp203, Arg526, and Asp542, hydrophobic bonds with Tyr299, Thr406, and Phe575, and electrostatic bonds with Asp327, Asp203, Met444, and Asp542. In conclusion, this research indicates that several chemical compounds from the rhizome of bangle have the potential to interact with the α-glucosidase receptor as antidiabetic agents.